THE EFFECT OF HOME PHARMACY CARE ON CLINICAL OUTCOMES AND QUALITY OF LIFE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Ali Nurrohim; Djoko Wahyono; Indri Hapsari (CV. Fahr Publishing, 2026)
Home Pharmacy Care (HPC) is a comprehensive, home-based pharmacy service designed to improve adherence, education, and monitoring for patients with Type 2 Diabetes Mellitus (T2DM) in order to achieve optimal clinical outcomes and a better quality of life. This study aims to evaluate the impact of implementing Home Pharmacy Care on clinical outcomes (such as HbA1c levels, blood pressure, and lipid profiles) as well as the quality of life of T2DM patients. The study used a quasi-experimental design with intervention and control groups, involving 60 patients at Mitra Siaga Hospital, Tegal Regency, Central Java. Clinical outcome and quality of life data were collected before and after the intervention using standardized instruments (WHOQOL-BREF for quality of life). The results of the study showed that the intervention group experienced significant improvements in all parameters compared to the control group (p < 0.05). In the intervention group, there was a mean decrease in HbA1c levels of -1.5% (p = 0.000), a decrease in systolic blood pressure of -14 mmHg (p = 0.001), and improvements in lipid profile characterized by a reduction in total cholesterol of -23 mg/dL (p = 0.002) and LDL by -17 mg/dL (p = 0.003). Additionally, the intervention group’s quality of life score showed a significant overall increase of +11.6 points (p = 0.001), particularly in the dimensions of physical health and social relationships. These findings suggest that Home Pharmacy Care has the potential to be an effective strategy for the sustainable management of T2DM patients.